Effect of topical berberine in murine cutaneous leishmaniasis lesions. (28th January 2022) - Calvo, Alba; Moreno, Esther; Aldalur, Irati; Sanmartín, Carmen; Larrea, Esther; González-Peñas, Elena; Irache, Juan Manuel; Espuelas, Socorro
Abstract: Objectives: More effective topical treatments remain an unmet need for the localized forms of cutaneous leishmaniasis (CL). The aim of this study was to evaluate the efficacy and safety of a topical berberine cream in BALB/c mice infected with Leishmania major parasites. Methods: A cream containing 0.5% berberine-β-glycerophosphate salt and 2.5% menthol was prepared. Its physicochemical and stability properties were determined. The cream was evaluated for its capacity to reduce lesion size and parasitic load as well as to promote wound healing after twice-a-day administration for 35 days. Clinical biochemical profile was used for estimating off-target effects. In vitro time-to-kill curves in L. major -infected macrophages and skin and plasma pharmacokinetics were determined, aiming to establish pharmacokinetic/pharmacodynamic relationships. Results: The cream was stable at 40°C for 3 months and at 4°C for at least 8 months. It was able to halt lesion progression in all treated mice. At the end of treatment, parasite load in the skin was reduced by 99.9% (4 log) and genes involved in the wound healing process were up-regulated compared with untreated mice. The observed effects were higher than expected from in vitro time-to-kill kinetic and plasma berberine concentrations, which ranged between 0.07 and 0.22 μM. Conclusions: The twice-a-day administration of a topical berberine cream was safe, able to stop parasite progression and improved the appearance of skin CL lesions. The relationship between drug plasma levels and in vivo effect was unclear.